2018
DOI: 10.1111/tid.12897
|View full text |Cite
|
Sign up to set email alerts
|

Sequential systematic anti‐mold prophylaxis with micafungin and voriconazole results in very low incidence of invasive mold infections in patients undergoing allogeneic hematopoietic stem cell transplantation

Abstract: Recipients of allogeneic hematopoietic stem cell transplantation (allo-HSCT) are at high risk for invasive mold infections (IMI). The goal of the study is to describe the incidence and outcome of IMI in patients after allo-HSCT in a large cohort of patients receiving anti-mold prophylaxis. We conducted a retrospective review of 988 consecutive adults who underwent allo-HSCT in our center from 2008 through 2014. Standard prophylaxis consisted of micafungin 150 mg IV daily from admission to day +7 ± 3 followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In accordance with the institutional standard of care, HCT recipients received antifungal prophylaxis with micafungin 150 mg i.v. once daily from the day of admission for HCT until day +7 post-transplantation (D+7) [19,20]. The dose of micafungin was chosen based on early studies suggesting administration of high doses of micafungin when used for antimold prophylaxis [21,22].…”
Section: Patients and Study Designmentioning
confidence: 99%
“…In accordance with the institutional standard of care, HCT recipients received antifungal prophylaxis with micafungin 150 mg i.v. once daily from the day of admission for HCT until day +7 post-transplantation (D+7) [19,20]. The dose of micafungin was chosen based on early studies suggesting administration of high doses of micafungin when used for antimold prophylaxis [21,22].…”
Section: Patients and Study Designmentioning
confidence: 99%
“…35,[46][47][48] Therefore, because of the high risk of aspergillosis in these patients, prophylaxis with drugs such as caspofungin, micafungin, voriconazole, posaconazole, liposomal amphotericin B (LAMB), and caspofungin may be beneficial. [48][49][50] Noteworthy, depending on the patient's condition, these drugs can have different effects; however, side effects and toxicity of these drugs may limit their longterm use. 51 Fontana and his colleagues reported that, although isavuconazole was used for prophylaxis patients with hematologic malignancies or hematopoietic cell transplant recipients to prevent IFI, the results showed an increase in the rate of IFI, especially invasive pulmonary aspergillosis in these patients.…”
Section: Aspergillosismentioning
confidence: 99%
“…Voriconazole is inactive in mucormycosis, and breakthrough infections during voriconazole exposure have been reported from retrospective evaluations and various case reports 109,203‐206 . However, prospective clinical trials on voriconazole prophylaxis did not confirm an increased incidence 207‐209 …”
Section: Resultsmentioning
confidence: 99%